The development of a positive youth programme (psy4life) module based on the yale attitude change approach - Getrude Cosmas; Chua Bee Seok; Shazia Iqbal Hashmi (Universiti Malaysia Sabah, 2016)
A positive youth development programme was developed based on the Yale Attitude Change Approach (Hovland, Janis & Kelly, 1953). The programme was named Psy4Life programme and it focuses on the two elements of positive youth development (i.e., psychological well-being & life effectiveness). The module consists of 13 activities to enhance participants’ psychological well-being and eight components of life effectiveness (i.e., achievement motivation, active initiative, self- confidence, leadership, emotional control, intellectual flexibility, time management & social competence). There were seven steps in the process of developing the programme module: 1) identify location and collect data from significant informants such as the village head, teachers, and youths; 2) create activities based on the information provided by the informants and by using the Yale Attitude Change approach as a guideline to develop the module; 3) Check the content validity of the module with the experts in the field of social psychology, 4) Modify and amend the module based on the experts’ evaluations, 5) conduct a one day training workshop for the facilitators that will conduct the structured activities; 6) implement the programme; 7) evaluate the effectiveness of the module by conducting the pre- and post-ttests design. This module can be used as a good platform to monitor the effects of structured activities on positive youth development programmes. It can also be used as a guideline for youth organisations to organize programmes that are relevant to the youths.